Cover Picture: Nanodiamond–TiO2 Composites for Heterogeneous Photocatalysis (ChemPlusChem 8/2013). Issue 8 (9th August 2013) - Pastrana‐Martínez, Luisa M.; Morales‐Torres, Sergio; Carabineiro, Sónia A. C.; Buijnsters, Josephus G.; Faria, Joaquim L.; Figueiredo, José L.; Silva, Adrián M. T.
<x xml:space="preserve">Abstract</x> The cover picture shows a schematic representation of oxidized nanodiamonds embedded into TiO2. To meet worldwide targets on water footprint reduction, these composites can be activated under sunlight to effectively degrade environmental water pollutants by direct oxidation with photogenerated holes as well as by the radical species formed from photoinduced holes or from photoexcited electrons. The composites prepared with nanodiamonds are more active than those prepared with microdiamonds (at comparable carbon contents) and an oxidation pretreatment of nanodiamonds is strongly recommended to obtain highly active photocatalysts, as demonstrated in the case of diphenhydramine degradation by A. M. T. Silva and co‐workers in their Full Paper on page 801 ff.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>